Prebiotic effects of palm kernel expeller oligosaccharides extract on intestinal microbiota and immune response in Salmonella-challenged broiler chicken - Rezaei, Siamak (2016)
The increased of the development of microbial resistance due to the use of antibiotics in animal feeds leads to search for a replacement for antibiotics. Prebiotics, which are non-digestible food ingredients, that beneficially affect the host by selectively stimulating the growth and/or activity of beneficial bacterial species residing in the colon had been reported as potential substitutes for antibiotics. Oligosaccharides from palm kernel expeller (PKE) have been reported to exhibit prebiotic effect in chicken. The aim of this study was to examine the periodic effects of oligosaccharides extract from PKE (OligoPKE) on immune system in broiler chickens. The first study examined the prebiotic effects of OligoOKE on growth performance, cecal microbiota and immune response in ninety 1-day-old Cobb500 broiler chicks. Dietary treatments were basal diet as control, basal diet plus 0.5% OligoPKE, and basal diet plus 1% OligoPKE. Chicken performance, caecal microbial quantification, all white blood cells type counted and immunoglobulins (IgA and IgM) were determined. Results showed that chickens fed OligoPKE supplemented diet had better FCR (P<0.05). Immunoglobulin and hematological data suggested that OligoPKE improved immune responses in broiler chickens, been more efficient during their younger age when their immune system was still not fully developed. The second experiment was designed to farther examine the prebiotic effects of OligoPKE on cecal microbiota including Salmonella population and immune response in chicks challenged with Salmonella enteritidis and Salmonella typhyimurium. A total of ninety 1-day-old chicks were randomly allocated to six treatment groups of 15 birds each. From day 1, chicks in three treatment groups were fed corn-soy based starter diet (22% CP and 3000 kcal ME/kg) and birds in the remaining three treatment groups received the same diet supplemented with 1% OligoPKE. On day 3, chicks in the first group within each dietary treatments were orally administered with 0.5 ml of S. enteritidis (1.0 x 109 CFU) and the second group with equal amount of S. typhimurium (1.0 x 109 CFU) while the third group was kept as control. OligoPKE supplementation reduced Salmonella population in both intact and challenged birds with stronger suppression effect in S. typhimurium group (P<0.05). Both challenged groups had higher level of plasma IgA, and OligoPKE supplementation elevated the plasma IgA response in S. typhimurium and jejunal IgA in S. enteritidis challenged birds. This result reaffirmed that OligoPKE acts as prebiotic, capable of enhancing beneficial cecal microbiota, suppressing pathogens and enhancing immune response in Salmonella challenged chicks. The third experiment was designed to examine the prebiotic effects of OligoPKE on cecal microbiota including Salmonella population and immune response in chicks challenged with different level of S. typhimurium. A total of one hundred and twenty 1-day-old chicks were randomly allocated to eight treatment groups of 15 birds each. From day 1, chicks in four treatment groups were fed corn-soy based starter diet (22% CP and 3000 kcal ME/kg) and birds in the remaining four treatment groups received the same diet supplemented with 1% OligoPKE. On day 3, chicks in the first groups within each dietary treatment were orally administered with 0.5 ml of S. typhimurium (1.0 x 108 CFU/mL), and the second groups were orally administered with 0.5 ml of S. typhimurium (1.0 x 106 CFU/mL) and third 0.5 ml of S. typhimurium (1.0 x 104 CFU/mL) respectively. While the fourth groups of each dietary treatments were kept intact. Samples were taken at day 10. Results of this experiment showed that OligoPKE supplementation reduced Salmonella population with all levels of contaminations in cecum and jejunum. In addition, OligoPKE increased the immunoglobulin A response in chicken in all the challenged groups. Data of immune gene expression showed that oligosaccharides could improve the total immunity (IL-2, IL-8, IL-10, IFN- γ, TNF- α and Muccin) of chicken. The last experiment was designed to examine the prebiotic effects of OligoPKE on cecal microbiota including Salmonella population and immune response in chicks challenged with S. enteritidis from three different sources, named ground, food and water. A total of eighty 1-day-old chicks were randomly allocated to eight treatment groups of 10 birds each. From day 1, chicks in four treatment groups were fed cornsoy based starter diet (22% CP and 3000 kcal ME/kg) and birds in the remaining four treatment groups received the same diet supplemented with 1% OligoPKE. On day 3, chicks in the first group within each dietary treatment received water contaminated with S. enteritidis (1.0 x 109 CFU/mL). While birds in second group were challenged with S. enteritidis (1.0 x 109 CFU/g) via contaminated feed. And the third group located in cages with contaminated floor with S. enteritidis (1.0 x 109 CFU/cm). While the fourth groups of each dietary treatments were kept intact. Results of this study showed that OligoPKE supplementation reduced Salmonella population in cecum and jejunum in both groups of contaminated water and feed with stronger effect in the contaminated water group (P<0.05). OligoPKE increased immunoglobulin A response in chicken in all challenged groups. Once again, the immune gene expression data showed that oligosaccharides could improve the total immunity (IL-2, IL-8, IL-10, IFN- γ, TNF- α and Muccin) of chicks. In conclusion, OligoPKE had shown its capability as a prebiotic by reducing pathogens in cecum and jejunum in Salmonella infected birds, increasing the immune response by effecting immunoglobulin production and the expression of immune related genes.